Early right ventricular function following trans-right atrial versus trans-right atrial, trans-right ventricular repair of Tetralogy of Fallot: Results of a prospective randomized study - Sachin Talwar; Abhishek Anand; Bharat Siddarth; Sivasubramanian Ramakrishnan; Shiv Kumar Choudhary; Balram Airan (Wolters Kluwer Medknow Publications, 2019)
Objective: We compared the pre- and post-operative right ventricular (RV) function by tricuspid annular plane systolic excursion (TAPSE) between trans-right atrial (t-RA) versus t-RA/RV (RA/RV) approach for the repair of Tetralogy of Fallot (TOF). Patients and Methods: Fifty consecutive patients, 1-15 years of age, undergoing intracardiac repair of TOF between September 2015 and June 2016 were randomized into two groups based on the approach for repair as follows: t-RA or t-RA/RV approach. TAPSE was used for the assessment of pre- and post-operative RV function. Results: Age, body surface area, preoperative saturation, cardiopulmonary bypass and aortic cross-clamp times, inotropic score, postoperative intensive care unit, and hospital stay were similar in both the groups. However, t-RA/RV group had significant mediastinal drainage (169 ± 163 ml vs. 90.6 ± 58.7 ml, P < 0.05) and pleural effusions (8 vs. 2 patients, P < 0.05), but had better relief of RV outflow tract gradients. The mean follow-up was 23 ± 6.7 (median 26, range 21-29) months. There were no differences in arrhythmias in either group up to the 1st month and at last follow-up. Preoperative TAPSE for t-RA and t-RA/RV was similar (1.49 ± 0.29 vs. 1.66 ± 0.34, P > 0.05) and so was the post-operative TAPSE at discharge (1.52 ± 0.30 vs. 1.43 ± 0.32, P > 0.05), at 1 month (1.6 ± 0.27 vs. 1.43 ± 0.032, P > 0.05) and at last follow-up (1.79 ± 0.15, median 1.8 vs. 1.72 ± 0.17, median 1.7 P > 0.05). Conclusion: Both t-RA and t-RA/RV approaches provide safe palliation for patients with TOF. A limited right ventriculotomy neither leads to deleterious effects on early RV function nor does it increase the incidence of arrhythmias at early follow-up. Larger studies with longer follow-up are needed to further address these issues.